Development of a Colloidal Gold-Based Immunochromatographic Strip for Rapid Detection of Severe Acute Respiratory Syndrome Coronavirus 2 Spike Protein - Li, Ge; Wang, Aiping; Chen, Yumei; Sun, Yaning; Du, Yongkun; Wang, Xun; Ding, Peiyang; Jia, Rui; Wang, Yanwei; Zhang, Gaiping (Frontiers in Immunology, 2021)
The outbreak and worldwide pandemic of the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have a significant impact on global economy and human health. In order to reduce the disease spread, 16 monoclonal antibodies (McAbs) again SARS-CoV-2 were generated by immunized mice with the spike protein receptor binding domain (RBD), which was expressed in Chinese hamster ovary cell (CHO). A colloidal gold-based immunochromatographic strip was developed with two McAbs to detect SARS-CoV-2 spike protein, which can play a potential role in monitoring vaccine quality. The strip is highly specific, detecting only SARS-CoV-2 spike protein, and does not show any non-specific reactions with syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV) and other coronavirus and influenza viruses. The strip detected subunit vaccine in our laboratory with a detection limit of spike protein of 62.5 ng/mL. This strip provides an effective method in monitoring vaccine quality by detecting the antigen content of spike protein.